(3GdWQGR GdefbhT aj eMGSf GdMHhTs - (3GHf YHO GdHGbj , eMeO Hf YHO GdHGbj GdHNGQj Gdecj, YdGA GdOjf CHh GdeYGdj,J (B993 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf ef UdUGd ef MeGeSfhf hHYO ajbhd GdYHO GdabjQ NWQ di ai gPg GdCjGe GdTQjaI Cf Chda QSGdI jSJOd HgG Ydi aVd GdMjhT s
(3BNQgG (B:s
(3hbGdhG cdG hGddg Hd CfgG JLdH Gdjge GdYjf hJPgH ef GdCKjQ s
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B123s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs